LncRNA in gastric cancer drug resistance: deciphering the therapeutic strategies - Liu, WeiChi; Wang, WeiFa (Frontiers in Oncology, 2025)
Gastric cancer (GC) is an exceedingly aggressive disease and ranks as the third leading cause of cancer-related deaths, which poses a huge health burden globally. Chemotherapy is commonly employed during the middle to advanced stages of cancer, although it faces frequent treatment failures attributed to drug resistance. Thus, it is imperative for researchers to identify potential targets for overcoming therapeutic resistance, thereby facilitating the development of novel anti-cancer agents for GC patients with advanced stages. Long noncoding RNAs (lncRNAs) are a diverse group of transcripts with limited protein-coding capacity, which have been recognized for functional molecules for regulating cancer progression including cell proliferation, metastasis, and drug resistance in GC. In this review, we examine the intricate molecular networks on the role of lncRNAs in drug resistance of GC. LncRNAs conferred cancer cell resistance to anti-cancer drug through various molecular mechanisms, therefore functioning as promising therapeutic targets for GC patients. Additionally, we discuss current advancements of strategies targeting lncRNAs in cancer therapy, which may pave the way for lncRNA-mediated precision medicine for this malignant disease.